Spatial distribution and risk assessment of dengue incidence at district level across major climatic zones in India - Meenu Mariya James; Karuppusamy Balasubramani; Praveen Balabaskaran Nina; Natarajan Gopalan; Sujit Kumar Behera (PLoS ONE, 2026)
Over the past decade, dengue incidence has been steadily increasing across the different climatic zones of India. The role of climatic variability in the spatial and temporal distribution of dengue at the district level across India is to be determined. District-level dengue incidence data from 2010 to 2022 were obtained from the National Centre for Vector-Borne Disease Control. Indian districts were categorized into eleven climatic zones based on the Köppen-Geiger climate classification scheme and subsequently grouped into three significant climatic zones (tropical, temperate and arid). Temporal trends were assessed using the Prais-Winsten regression model that accounted for serial autocorrelation, while climate zonal differences in annual incidence were evaluated using Kruskal-Wallis tests and pairwise comparisons. The global Moran’s I test was used to assess overall spatial autocorrelation, followed by Anselin’s local Moran’s I test to identify clustering and hotspots of dengue incidences at the district level. There is significant heterogeneity in dengue distribution across the districts in India. Prais-Winsten regression analysis shows the strongest upward trend in dengue incidence in polar tundra (ET) zone [AIR = 126.9%; p = 0.01], temperate, no dry season, hot summer (Cfa) zone [AIR: 94.8%; p = 0.01], and cold, no dry season, warm summer (Dfb) zone [AIR = 85.1%; p < 0.001], indicating a substantial intensification of dengue transmission even in cooler climatic regions. Kruskal-Wallis tests confirmed persistent and significant disparities between tropical, temperate, and arid regions. Spatial analysis revealed clustering (Global Moran’s I = 0.06, p < 0.001), with 31 high-incidence clusters concentrated primarily in the semi-arid regions of Punjab and Haryana, and humid regions of Tamil Nadu and Kerala. Overall, the identified clustering of high-incidence districts in semi-arid and humid regions, along with the upward trends in multiple climatic zones, highlights an urgent need to embed climate-sensitive planning, early warning systems, and geographically targeted vector-control measures into India’s dengue prevention framework.